2017
DOI: 10.1016/j.bandl.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Sleep spindles during a nap correlate with post sleep memory performance for highly rewarded word-pairs

Abstract: The consolidation of new associations is thought to depend in part on physiological processes engaged during non-REM (NREM) sleep, such as slow oscillations and sleep spindles. Moreover, NREM sleep is thought to selectively benefit associations that are adaptive for the future. In line with this, the current study investigated whether different reward cues at encoding are associated with changes in sleep physiology and memory retention. Participants' associative memory was tested after learning a list of arbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 36 publications
7
32
0
Order By: Relevance
“…With regard to the neurophysiological correlates of SWSdependent consolidation, we found significant correlations between frontocentral slow spindle power as well as frontal (F3) fast spindle power and postsleep memory performance. These results are in line with prior studies showing that sleep spindle density constitutes a sensitive measure of system consolidation processes occurring during NREM sleep (Mednick et al, 2013;Studte et al, 2015;Studte et al, 2017). It is assumed that temporally coupled spindle-ripple events provide a physiological mechanism for a fine-tuned hippocampal-neocortical information flow (Diekelmann & Born, 2010).…”
Section: Neurophysiological Correlates Of Memory Consolidationsupporting
confidence: 91%
“…With regard to the neurophysiological correlates of SWSdependent consolidation, we found significant correlations between frontocentral slow spindle power as well as frontal (F3) fast spindle power and postsleep memory performance. These results are in line with prior studies showing that sleep spindle density constitutes a sensitive measure of system consolidation processes occurring during NREM sleep (Mednick et al, 2013;Studte et al, 2015;Studte et al, 2017). It is assumed that temporally coupled spindle-ripple events provide a physiological mechanism for a fine-tuned hippocampal-neocortical information flow (Diekelmann & Born, 2010).…”
Section: Neurophysiological Correlates Of Memory Consolidationsupporting
confidence: 91%
“…On average, the performance of the animals was also higher for the large reward location compared to small for both delays. These results are consistent with the studies carried in human showing a selective enhancement of memory for salient experiences, including the expectation of a higher value outcome, after both a short or long retention delay (Igloi et al 2015;Gruber et al 2016;Studte, Bridger, and Mecklinger 2017). Moreover, after 2h delay, we observed that overall the animals directly repeated visits to the target arm with a lower probability than expected by chance.…”
Section: Discussionsupporting
confidence: 93%
“…Relevant material is preferentially remembered even in comparison to neutral material occurring concomitantly or close in time. Moreover, the enhanced retention of such experiences correlates with the increased hippocampal activity during learning, as well as post learning (Rauchs et al 2011;Gruber et al 2016) and with the increased occurrence of slow wave sleep and spindles in the cortex (Stickgold and Walker 2013;Igloi et al 2015;Gruber et al 2016;Studte, Bridger, and Mecklinger 2017) . Thus, the enhanced retention of relevant experiences is an active selective process relying on the modulation of the neuronal activity supporting both encoding and consolidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating different prioritization cues; namely future utility (Wilhelm et al, 2011;Studte et al, 2017) and directed forgetting Alger et al, 2019) have similarly found that sleep spindles act selectively. These findings, taken together with the results reported here, represent evidence for an emerging hypothesis that sleep spindles are involved in selective memory consolidation based on encoding-related salience tags.…”
Section: Discussionmentioning
confidence: 99%